Diseño de una red híbrida basada en las tecnologías wifi-plc para la implementación en el barrio Víctor Emilio Valdivieso. - Mocha Brito, Patricia Alexandra (2016)
There are many marginal sectors in Loja city that don’t enjoy telecommunications services as internet and telephony due to its geographical location. The new communication technologies between their approaches seek to reduce the digital divide and thus find the same technologies that are better adapted to the reality of each city according to your needs In this thesis we try to find analyze and design a hybrid network with the ability to transmit data and voice using PLC technology. To carry out this project we choose the sector Victor Emilio Valdivieso, which its located at Km 7 ½ old road to Canton Catamayo, It does not have a complete telecommunications infrastructure and Internet access is limited by the coverage in various suppliers through antennas point - multipoint. The development of this work is concentrated to the fulfillment of the following objectives: To study the characteristics, standards, protocols and regulations governing the use and operation of WIFI-PLC, necessary to size the design features of the network depending on the services to be provided. Design based on certain characteristics and dimensioning of VoIP services and Internet, WIFI-PLC network on the object of study. "Victor Emilio Valdivieso" Sector Select the necessary equipment for the implementation of the network based on the characteristics of raised, capable of meeting the requirements and services outlined in the design, and develop a design reference budget.